Caribbean Women and Their Art: An Encyclopedia - Snodgrass, Mary Ellen (Rowman & Littlefield Publishers, 2019)
Overlooked in the history of artistic endeavors are the contributions of female writers, painters, and crafters of the Caribbean. The creative works by women from the Caribbean proves to be as remarkable as the women themselves. In Caribbean Women and Their Art: An Encyclopedia, Mary Ellen Snodgrass explores the rich history of women’s creative expression by examining the crafts and skill of over 70 female originators in the West Indies, from the familiar islands—Jamaica, Haiti, Cuba, Puerto Rico—to the obscurity of Roatan, Curaçao, Guanaja, and Indian Key. Focusing particularly on artistic style during the arrival of Europeans among the West Indies, the importance of cultural exchange, and the preservation of history, this book captures a wide variety of artistic accomplishment, including Folk music, acting, and dance Herbalism and food writing Sculpture, pottery, and adobe construction Travel writing, translations, and storytelling Individual talents highlighted in this volume include dancer Katherine Dunham, storyteller Louise Bennett-Coverley, paleontologist Sue Hendrickson, dramatist Maryse Condé, herbalist and memoirist Mary Jane Seacole, ballerina and choreographer Alicia Alonso, and athor Elsie Clews Parsons. Each entry includes a comprehensive bibliography of primary and secondary sources, as well as further readings on the female artists and their respective crafts. This text also defines and provides examples of technical terms such as ramada, slip, hematite, patois, and mola. With its informative entries and extensive examinations of artistic talent, Caribbean Women and Their Art: An Encyclopedia is a valuable resource for students, scholars, and anyone interested in learning about some of the most influential and talented women in the arts.